A rare case of subclinical hyperthyroidism due to Graves’ disease with papillary thyroid carcinoma in a young female - Datta, Mita; Islam, Mohammad Aminul; Sultana, Nusrat; Fariduddin, Md. (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
A 36-year-old lady presented with convincing symptoms of hyperthyroidism with a swelling in front of her neck for the last 3 months, but she denied any fever, flu-like illness, or pain over it. On examination, there was a non-tender (2 X 2) cm2 nodule in the left lobe of the thyroid, firm in consistency, not fixed to the surrounding structure, and no cervical lymphadenopathy. Investigations showed suppressed TSH, normal FT4 and FT3, and positive TRAb. USG of the thyroid showed a nodule (2.2 x 1.3 x 2 cm3) with a TIRADS score of 4 in the lower pole of the left lobe of the thyroid; thyroid scan revealed a warm nodule in the left lobe. FNAC showed Bethesda category VI. Total thyroidectomy was safely performed. Histopathology confirmed the case as a well-differentiated, classical variety of papillary thyroid cancer. One month later, she visited the endocrinologist with TSH 73.3 mU/L, thyroglobulin 3.52 ng/mL, negative anti-thyroglobulin antibody, USG of the neck showing no remnant, thyroid scan showing a small remnant in the thyroid bed. So, the patient was categorized into the American Thyroid Association-defined “indeterminate response” category. Levothyroxine was started again, and she was kept under regular follow-up. [J Assoc Clin Endocrinol Diabetol Bangladesh, 2025;4(Suppl 1): S52]